Reforming innercity bus transportation in a developing country: a passenger-driven model - Andaleeb, Syed Saad; Haq, Mahmudul; Ahmed, Rubina I (© National Center for Transit Research (NCTR), University of South Florida, 2016)
This is an Open Access Article. It is published by Journal of Public Trasportation and the definite version is available at: http://dx.doi.org/10.5038/2375-0901.10.1.1